Lactobacillus acidophilus as a Dietary Adjunct in Dahi and Yogurt - Appalo Eleven S (Department of Dairy Science, College of Veterinary and Animal Sciences, 1995)
An experiment was conducted to study the beneficial effect of incorporating L. acidophilus in dahi and yogurt as a dietary adjunct. An attempt was also made to find out the bile tolerance of L. acidophilus and other lactic acid bacteria.